Activated Protein C Inhibits Proliferation and Tumor Necrosis Factor α-Stimulated Activation of p38, c-Jun NH2-Terminal Kinase (JNK) and Akt in Rheumatoid Synovial Fibroblasts - Sohel M. Julovi; Kaitlin Shen; Kelly McKelvey; Nikita Minhas; Lyn March; Christopher J. Jackson (BMC, 2013)
Abstract Synovial fibroblast proliferation Is a hallmark of the Invasive pannus in the rheumatoid joint. Activated protein C (APC) is a natural anticoagulant that exerts antiinflammatory and cyto-protective effects in various diseases via endothelial protein C receptor (EPCR) and proteinase-activated receptor (PAR)-mediated pathways. In this study, we investigated the effect and the underlying cellular signaling mechanisms of APC on proliferation of human rheumatoid synovial fibroblasts (RSFs). We found that APC stimulated proliferation of mouse dermal fibroblasts (MDFs) and normal human dermal fibroblasts (HDFs) by up to 60%, but robustly downregulated proliferation of RSFs. APC induced the phosphorylation of extracellular signal-regulated protein kinase (ERK) and enhanced expression of p21 and p27 in a dose-dependent manner in RSFs. The latter effect was inhibited by pretreatment with the ERK inhibitors PD98059 and U0126 but not by p38 inhibitor SB203580. In addition, APC significantly downregulated tumor necrosis factor (TNF)α-stimulated cell proliferation and activation of p38, c-Jun NH2-terminal kinase (JNK) and Akt in RSFs. These results provide the first evidence that APC selectively inhibits proliferation and the inflammatory signaling pathways of RSFs. Thus, APC may reduce synovial hyperplasia and pannus invasion in rheumatoid arthritis.